PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII4 SMP NEGERI 20 PEKANBARU - Inalda, Avisha Trinanda; Anggraini, Rini Dian; ', Jalinus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This classroom action research is aimed at improving learning process and improving math learning outcomes by implementing Cooperative Learning Model with Structural Two Stay Two Stray (TSTS) Approach. The research subjects are 40 heterogenous academic ability level students of the VIII4 class of State Junior High School 20 Pekanbaru in academic year of 2015/2016. The research consisted of two cycles in which each cycle consisted of four phases, i.e; namely planning, implementing, observing, and reflecting. By the end of a cycle, daily test was held. The data was collected by means of observation and daily test. The action success indicators were if there is learning process improvement and the increasing number of students passing Minimun Completeness Criteria (MCC) in daily test I and daily test II. The research shows that teachers and students’ activities were conducted well as planned. Most of the students participated actively in the learning process e.g. discussing, presenting student’s worksheet, responding to classmate’s presentation, and drawing the lesson conclusion. Additionally, the students afforded to answer the written test given by teacher well. Therefore, it can be said that improvement of learning process took place in every meeting. Furthermore, the number of students passing the MCC on base score, daily test I (first cycle), daily test II (second cycle) were respectively 35%, 52,5%, and 77,5%. The percentage of MCC achievement also indicates the increase after the implementation, thus it can be said that the students’ learning outcomes also increse. Finally, the research also shows that cooperative learning model with structural two stay two stray (TSTS) approach can improve math learning process and learning outcomes of VIII4 class students at State Junior High School 20 Pekanbaru.Key Words: Math Learning Outcomes, Cooperative Learning Model with Structural Two Stay Two Stray (TSTS) Approach, Classroom Action Research.